The New Anthology of American Poetry : Modernisms: 1900-1950 - Travisano, Thomas, 1951-; Roman, Camille, 1948-; Axelrod, Steven Gould, 1944- (Book collections on Project MUSE., 2003)
Overview: Steven Gould Axelrod, Camille Roman, and Thomas Travisano continue the standard of excellence set in Volumes I and II of this extraordinary anthology. Volume III provides the most compelling and wide-ranging selection available of American poetry from 1950 to the present. Its contents are just as diverse and multifaceted as America itself and invite readers to explore the world of poetry in the larger historical context of American culture. Nearly three hundred poems allow readers to explore canonical works by such poets as Elizabeth Bishop, Robert Lowell, and Sylvia Plath, as well as song lyrics from such popular musicians as Bob Dylan and Queen Latifah. Because contemporary American culture transcends the borders of the continental United States, the anthology also includes numerous transnational poets, from Julia de Burgos to Derek Walcott. Whether they are the works of oblique avant-gardists like John Ashbery or direct, populist poets like Allen Ginsberg, all of the selections are accompanied by extensive introductions and footnotes, making the great poetry of the period fully accessible to readers for the first time.